Rotavirus contamination of surface waters from the northwest of Argentina - Prez, Verónica Emilse (2020)
Fecal pollution of water is a serious concern because it is associated with the transmission of pathogens. The aim of this study was to analyze the occurrence of group A rotavirus (RVA) in surface waters from the Arias–Arenales River in Salta, a northern city in Argentina, and to define possible sources of fecal viral pollution. A total of 116 water samples were analyzed and RVA was detected in 3.4% (95% CI: 0.1–7.0%), with concentrations ranging from 1.9 × 105 to 3.8 × 106 genome copies per liter. RVA strains were characterized as G1P[8], G4P[8] and G9P[8], which are common genotypes circulating in the local population. The Arias–Arenales River presented unusual and sporadic contamination by RVA, originated from stormwater discharges and a variety of non-identified sources, and support the essential need of viral indicators for enhanced monitoring of water quality.